1999
DOI: 10.1016/s0266-352x(99)00016-6
|View full text |Cite
|
Sign up to set email alerts
|

Displacement charts for slopes subjected to seismic loads

Abstract: Earthquake events in recent years have brought about renewed interest in analyses of slopes subjected to seismic loads. These loads have been accounted for traditionally by using quasistatic loads. Such analyses do not provide any information about permanent displacements, and they neglect the history of seismic shaking. The analysis presented in this note is based on the rigid block displacement technique. A rotational mechanism of slope failure, caused by horizontal shaking, is considered. Yield acceleration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the case of intact slopes with a low value of ϕ, [9] found that for high values of K h , the failure mechanism passes below the slope toe (see Figure 2b). The results reported here in our paper include both types of failures.…”
Section: Derivation Of the Analytical Solutionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the case of intact slopes with a low value of ϕ, [9] found that for high values of K h , the failure mechanism passes below the slope toe (see Figure 2b). The results reported here in our paper include both types of failures.…”
Section: Derivation Of the Analytical Solutionmentioning
confidence: 94%
“…In the large body of literature on limit analysis applied to slopes subject to seismic excitation (e.g. [2][3][4][5][6][7][8][9]), there is no provision to take into account the presence of cracks. In this paper, an analytical method based on *Correspondence to: S. Utili, School of Engineering, University of Warwick, CV4 7AL Coventry, U.K. function of slope characteristics (ϕ and β values).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations of displacements of slopes subjected to seismic acceleration are based here on the concept of a sliding block (Newmark 1965). Here, the consideration is modified to include rotation of the failing mass, much like that in the paper of Chang et al (1984), You and Michalowski (1999), and Michalowski and You (2000). While the specific mechanism considered here is one rotating block, the concept can be applied to multi-block mechanisms as demonstrated in Michalowski (2007).…”
Section: Sliding Block Analysismentioning
confidence: 99%
“…In addition, earthquake loading can influence the shape of failure surface, particularly when tension cracks are present. Earthquake-induced landslides are among the most destructive slope movements and there is a large body of literature on limit analysis or other methods applied on landslides triggered by seismic activities (Chang et al, 1984, Ling and Leshchinsky, 1995, Crespellani et al, 1998, Cao and Zaman, 1999, You and Michalowski, 1999, Loukidis et al, 2003, Chen and Liu, 1990, Yang and Chi, 2014. Seismic shaking can directly trigger slope failures and at the same time cause damage within the slope material, predisposing it to successive failures under different triggering factors or earthquakes of smaller magnitude.…”
Section: Increase Of Driving Forcesmentioning
confidence: 99%